Evaluation of the suitability of peat land for plantation commodities in Sambas District, West Kalimantan - Sangkala, Sangkala; Heriyansah, Heriyansah; Sunardi, Sunardi (Anjoro: International Journal of Agriculture and Business, 2023)
This research aims to determine the potential of peat land for the development of plantation crops which describes the potential of the land. This research is located in Sambas District, Sambas Regency, West Kalimantan. The number of soil sampling location are 10 sampling points. The initial activity of the program is collection of information about the status of peatland capability followed by a peatland suitability analysis to determine the types of plantation crops that are suitable for development. The data obtained include rainfall, temperature, topography, solum depth, water permeability, drainage conditions, erosion sensitivity, texture, C-Organic Content, Nitrogen, Phosphorus, Potassium, CEC and pH. The analysis of the suitability of the actual conditions of the land with the types of plantation crops, namely oil palm and rubber, is highly developed in Sambas sub-district because there are no growth limiting factors. Other plantation commodities that have the potential to be developed but have growth limiting factors (S3) are coconut, cloves, coffee, cocoa, tea, tobacco, cashew, nutmeg and vanilla which have 1 limiting factor, while cotton, melinjo and kapok commodities are categorized as highly inappropriate (N) with the heaviest limiting factor of water availability. The limiting factor of rainfall can be overcome through the creation of basins and drainage channels so that excess water in the land can be anticipated, while the improvement efforts that can be carried out on acid soils are the application of dolomite lime to increase the pH of the soil so that it is in accordance with the requirements of plant growth.